2004
DOI: 10.1080/02724980343000657
|View full text |Cite
|
Sign up to set email alerts
|

7–11–Year–Old Children Show an Advantage for Matching and Recognizing the Internal Features of Familiar Faces: Evidence against a Developmental Shift

Abstract: Adults are better at recognizing familiar faces from the internal facial features (eyes, nose, mouth) than from the external facial features (hair, face outline). However, previous research suggests that this "internal advantage" does not appear until relatively late in childhood, and some studies suggest that children rely on external features to recognize all faces, whether familiar or not. We use a matching task to examine face processing in 7-8- and 10-11-year-old children. We use a design in which all fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 30 publications
5
41
1
Order By: Relevance
“…reliance on second-order relational features, or the extent to which infants and neonates show a reliance on the spatial configuration of facial features. Bonner and Burton (2004) reported recognition advantages for discriminating familiar faces from inner vs. outer features in children as young as 7 years that was comparable to that of adult subjects (Nachson & Shechory, 2002). Similarly, Flin (1985) reported an advantage for face recognition in upright compared to inverted faces in children as young as 7 years of age.…”
Section: Introductionmentioning
confidence: 67%
“…reliance on second-order relational features, or the extent to which infants and neonates show a reliance on the spatial configuration of facial features. Bonner and Burton (2004) reported recognition advantages for discriminating familiar faces from inner vs. outer features in children as young as 7 years that was comparable to that of adult subjects (Nachson & Shechory, 2002). Similarly, Flin (1985) reported an advantage for face recognition in upright compared to inverted faces in children as young as 7 years of age.…”
Section: Introductionmentioning
confidence: 67%
“…Research with typical adults consistently shows that masking internal features (eyes, nose, mouth) of familiar faces is more detrimental for recognition and face matching than masking external features (hair, chin, ears; Ellis, Shepherd & Davies, 1979;Young, Hay, McWeeny, Flude & Ellis, 1985). This pattern is not evident for unfamiliar faces and there is no change in the way that internal and external features contribute to unfamiliar face processing across development (Campbell, Walker & Baron-Cohen, 1995;Campbell et al, 1999, Bonner & Burton, 2004.…”
Section: )mentioning
confidence: 99%
“…The current task uses the internal versus external feature paradigm to explore face matching by individuals with WS replicating a procedure already used with typically developing individuals (Bonner & Burton, 2004). Whole face targets are eliminated and the stimuli incorporate different orientations to avoid pattern matching strategies.…”
Section: )mentioning
confidence: 99%
“…Inner face features, such as the eyes, nose and mouth, are more important than external features for recognizing and matching familiar faces (Bruce, 1988;Ellis et al, 1979;Young et al, 1985). Developmental studies have found that adult-like processing of inner features is not achieved until between 10 and 15 years of age (Campbell, Coleman, et al, 1995;Campbell, Walker, & Baron-Cohen, 1995;Want, Pascalis, Coleman, & Blades, 2003; although see Bonner & Burton, 2004). Some authors have argued that perceptual expertise is required to successfully encode inner face features.…”
mentioning
confidence: 99%